Handbook of Outpatient Medicine - Sydney, Elana; Weinstein, Eleanor; Rucker, Lisa M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The practice of outpatient medicine in the 21st century has become fast-paced and challenging. The busy practitioner learns to make accurate decisions regarding diagnoses and treatments, individualizing them based on the patients$1 (Bparticular characteristics and desires. Patients typically present with more than one issue, spanning from wanting information about a vaccine to having symptoms of an acute and serious infectious disease, while also needing care of their chronic conditions. In order to function in a timely manner, the provider needs a reliable resource to aid in making efficient decisions. This text is designed to fulfill this purpose. Now fully revised and expanded, Handbook of Outpatient Medicine, 2e provides a quick, portable, algorithm-based guide to diagnosis and management of common problems seen in adult patients. Written by experienced primary care practitioners, this text emphasizes efficient decision-making necessary in the fast-paced realm of the medical office. It covers general considerations such as the physical examination, care of special populations, and pain management and palliative care. It also focuses on common symptoms and disorders by system, including endocrine, respiratory, cardiac, orthopedic, neurologic, genitourinary, and gynecologic. For each disorder, symptoms, red flags, algorithms for differential diagnosis, related symptoms and findings, laboratory workup, treatment guidelines, and clinical pearls are discussed. One of the major updates in this edition is a chapter dedicated to COVID-19. This chapter focuses on COVID-19 diagnosis, care and sequelae, including what to do after discharge from the hospital. Since the global pandemic has affected medicine as a whole, many of the chapters also discuss COVID-19 as a differential diagnosis. Newer and higher quality photos have also been added in several chapters to help illustrate techniques more efficiently, including new imaging modalities for chest pain.s
Keywords: Primary care (Medicine).; Family medicine; Primary Care Medicine; General Practice and Family Medicine; Ambulatory Care -- methods; Clinical Decision-Making; Handbook